Nicole Solomon: capstone - Solomon, Nicole, artist (Colorado State University. Libraries, 2025)
The artist's statement: Welcome to me and my work! I am a graphic designer inspired by my religion and heritage, Brazil, and the many languages that shape our world—especially American Sign Language (ASL). For me, art is a way to communicate across cultures and experiences, creating bright visuals that are both meaningful and accessible. I truly believe in the principle of "less is more," letting simplicity guide my work so that every element has purpose and impact without being too overwhelming. I really enjoy working with a mix of digital tools and traditional techniques, as I grew up in a traditional environment, exploring color, typography, and unique layouts to bring ideas to life. My process usually begins with research and reflection, often drawing from cultural and personal experiences, before moving into concepts and designs. To me, each piece is an opportunity to show or tell a story. Much of my inspiration comes from my heritage; there’s such a fun and expressive energy in Brazilian culture, and the beauty of language in all its forms, that is just begging to be released. I aim to create work that communicates directly and emotionally, fixing gaps and sparking connections between people around the world. Through my designs, I aim to leave a lasting impression while keeping things simple, intentional, and thoughtful. Whether collaborating with clients or exploring personal projects, my work reflects who I am and the world I want to share with others.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design